Ecological features of saiga Saiga tataricaL. var.tatarica of Betpakdaly population of the Central Kazakhstan - Turlybekova, G.K.; Turlybekova, A.A.; Akhmetova, A.N.; Gorbacheva D.А. (Fundamental and Experimental Biology, 2017)
In the article the ecological features and biological characteristics of saiga — Saiga tataricaL. var. tatarica of Betpakdaly population dwelling in semi-deserts and dry steppe zones are considered. Comparing to appearance, Saiga is quite different from other animals living in steppe area. Its external and internal appearance, nasal part structure, behavior and fodder resources are described in the article. The map of migration of saiga on Betpakdaly is shown; also some plant species of steppe zone eaten by saiga in different seasons of year are presented. So, saiga in Kazakhstan eats perennial and annual herbaceous plants which referred to 17 families and 81 species. Gender and age structure, population dynamics of saiga of Betpakdaly population of Central Kazakhstan are shown.